2022
DOI: 10.1002/jsfa.11725
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of benzoic acid and cinnamic acid hydroxyl derivatives on polyphenol oxidase: activity, action mechanism, and molecular docking

Abstract: BACKGROUND: Polyphenol oxidase (PPO) is considered to have a key role in the food industry because it initiates enzymatic browning in the processing and storage of fruit and vegetables. Increasing numbers of benzoic and cinnamic acid derivatives have been found to be efficient inhibitors of polyphenol oxidase, but a comparison study on activity and action mechanism is lacking. In this study, 18 benzoic acid and cinnamic acid hydroxy derivatives were selected and investigated. RESULTS: Three substrates, four ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…These findings suggested that the obtained, purified wheat PPO had substrate-binding sites with a high affinity for o-diphenolic (e.g., catechol and caffeic acid) and triphenolic (e.g., gallic acid and pyrogallic acid) structures. In contrast to previous reports, protocatechuic acid showed a lower affinity for wheat PPO, despite its o-diphenolic structure [ 18 ]. The phenolic compounds in green tea were more likely to become the substrate of wheat PPO because of their polyhydroxy structure, especially epigallocatechin gallate (EGCG).…”
Section: Resultscontrasting
confidence: 99%
“…These findings suggested that the obtained, purified wheat PPO had substrate-binding sites with a high affinity for o-diphenolic (e.g., catechol and caffeic acid) and triphenolic (e.g., gallic acid and pyrogallic acid) structures. In contrast to previous reports, protocatechuic acid showed a lower affinity for wheat PPO, despite its o-diphenolic structure [ 18 ]. The phenolic compounds in green tea were more likely to become the substrate of wheat PPO because of their polyhydroxy structure, especially epigallocatechin gallate (EGCG).…”
Section: Resultscontrasting
confidence: 99%
“…However, CQA is a good substrate for PPO and tends to be oxidized to be CQAQ to induce browning. Sun et al (2022) also found that 3,4,5trihydroxybenzoic acid was a PPO inhibitor rather than a substrate. Further research is required to uncover this contradiction.…”
Section: Novel Ppo Inhibitorsmentioning
confidence: 92%
“…Sun et al. (2022) also found that 3,4,5‐trihydroxybenzoic acid was a PPO inhibitor rather than a substrate. Further research is required to uncover this contradiction.…”
Section: Intervention Strategies For O‐quinone and O‐quinone‐induced ...mentioning
confidence: 98%
See 1 more Smart Citation